PEMETAAN ZONA KERENTANAN GERAKAN MASSA DENGAN METODE Analytic Hierarchy Process (AHP) DI DESA TENGKLIK DAN SEKITARNYA, KECAMATAN TAWANGMANGU KABUPATEN KARANGANYAR, PROPINSI JAWA TENGAH - , Rya Herfibriani; , Dr. Tarsisius Hani Handoko, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
PT Matahari Department Store Tbk is one of the companies competing in the retail business within Indonesia. Competition in the retail industry has increased remarkably coinciding with free trading being more open, shown by the addition of several foreign department stores into the Indonesian retail industry. To maintain a competitive foothold and stay in front of their competitors, PT Matahari Department Store Tbk has developed their own capabilities and resources consistent with their Cost Leadership strategy. In this study will be done an analyis of PT Matahari Department Store Tbkâs capabilities and resources using VRIO analysis, which is an analysis focused on the internal conditions within a company. Capabilities and resources within a company can be created from the activities done by PT Matahari Department Store Tbk. This study also analize using Value Chain analysis. After conducting analysis using VRIO and describing the main and supporting activities within the company, then the competitive advantages of PT Matahari Department Store Tbk is able to be identified. An advantage that can sustain within the competition in the retail industry is an advantage that has the criteria included in the VRIO analysis, that are valuable, rare, inimitable and organized. An advantage that fulfills the four criterias stated above is usually known as a Sustainable Competitive Advantage.